Effect of solvent-substrate noncovalent interactions on the diastereoselectivity in the intramolecular carbonyl-ene and the staudinger [2+2] cycloaddition reactions - Jain, Shailja; Vanka, Kumar (Journal of Physical Chemistry A, 2020)
Noncovalent interactions (NCIs) have been identified as important contributing factors for determining selectivity in organic transformations. However, cases where NCIs between solvents and substrates are responsible for a major extent for determining selectivity are rare. The current computational study with density functional theory identifies two important transformations where this is the case: the intramolecular carbonyl-ene reaction and the Staudinger [2 + 2] cycloaddition reaction. In both cases, the role of explicit solvent molecules interacting non-covalently with the substrate has been taken into account. Calculations indicate that the diastereomeric ratio would be 95.0:5.0 for the formation of tricyclic tetrahydrofuran diastereomers via the intramolecular carbonyl-ene reaction and 94.0:6.0 for the formation of the triflone diastereomers via the Staudinger [2 + 2] cycloaddition reaction, which corroborates with the experiment. Interestingly, in both the cases, the calculations indicate that noninclusion of explicit solvent molecules would lead to only a small difference between the competing transition states, which leads to the conclusion that solvent-substrate NCIs are the major cause for diastereoselectivity in both the cases considered.